Enhanced 1.53 µm fluorescence and energy transfer mechanism in tellurite glasses doped with Er3+/Ce3+/Yb3+. (August 2015) - Yang, Fengjing; Huang, Bo; Wu, Libo; Peng, Shengxi; Qi, Yawei; Zhou, Yaxun
Abstract: Tellurite glasses (TeO2 –ZnO–La2 O3 ) doped with Er 3+, Er 3+ /Ce 3+ and Er 3+ /Ce 3+ /Yb 3+ have been prepared using the melt-quenching technique, and the absorption spectra, fluorescence and up-conversion emission spectra together with the differential scanning calorimeter (DSC) curves and X-ray diffraction (XRD) patterns were measured to evaluate the effects of Ce 3+ and Yb 3+ introduction on the 1.53 µm band spectroscopic properties of Er 3+, thermal stability and structural nature of glass hosts. The Judd–Ofelt intensity parameters Ω t ( t =2, 4, 6), spontaneous emission probabilities, radiative lifetimes and branching ratios of several Er 3+ transitions were calculated from the measured absorption spectra based on the Judd–Ofelt theory. The co-doping with Ce 3+ was effective on the suppression of up-conversion emission of Er 3+ owing to the phonon-assisted energy transfer: Er 3+ : 4 I11/2 +Ce 3+ : 2 F5/2 →Er 3+ : 4 I13/2 +Ce 3+ : 2 F7/2, while the co-doping with Yb 3+ had the effect of obviously increasing the Er 3+ population at 4 I11/2 level via the resonant energy transfer: Yb 3+ : 2 F5/2 +Er 3+ : 4 I15/2 →Yb 3+ : 2 F7/2 +Er 3+ : 4 I11/2, both of which contributed the effective enhancement of 1.53 µm fluorescence emission. The quantitative studies were carried out to elucidate the energy transfer mechanism by calculating the microscopic parameters and phonon contribution ratios. The glass transition temperature ( T g ), crystallization onset temperature ( T x ) and the difference Δ T ( = T x − T g ), which characterize the thermal stability of glass host, increased with the Ce 3+ and Yb 3+ co-doping and for all glass samples the value of Δ T is larger than 145 °C. The glass structural nature was demonstrated from the measured XRD patterns with no sharp diffraction peaks. The results of the present work indicated that the prepared Er 3+ /Ce 3+ /Yb 3+ co-doped tellurite glass is a potential material for developing broad-band and high-gain optical amplifiers and other optical devices. Highlights: Er 3+ /Ce 3+ /Yb 3+ co-doped tellurite glasses were prepared using melt-quenching method. The prepared RE doped tellurite glasses exhibited good thermal stability with Δ T >145 °C. The 1.53 µm fluorescence of Er 3+ increased greatly with the addition of Ce 3+ and Yb 3+ . The ET mechanisms between Yb 3+ /Er 3+ and Er 3+ /Ce 3+ were investigated quantitatively.